The role of project-based ethno-didactics of mathematics learning toward pre-service elementary teachers’ perspectives, mathematical, and didactic knowledge - Putra, Zetra Hainul; Hermita, Neni; Alim, Jesi Alexander; Dahnilsyah, Dahnilsyah; Gunawan, Yahya (Frontiers in Education, 2025)
Research indicates that both pre-service and in-service teachers struggle with explaining mathematical concepts to elementary school students due to insufficient mathematical and didactic knowledge. This study aims to examine the effects of Project-Based Ethno-Didactics of Mathematics Learning on pre-service elementary teachers’ perspectives, mathematical knowledge, and didactic knowledge. This is a quasi-experimental study with a one-group pre-test and post-test design. The participants in the study were 39 s-year pre-service elementary teachers from a public university in Riau province, Indonesia, enrolled in an elementary school teacher education program. A non-parametric statistical test (Wilcoxon test) was utilized to analyze the data and test the hypothesis. The findings of this study revealed that Project-Based Ethno-Didactics of Mathematics Learning has a significant effect on pre-service elementary teachers’ perspectives, mathematical knowledge, and didactic knowledge. However, some areas of mathematical and didactic understanding showed only moderate gains, suggesting the need for deeper integration of content-specific ethno-didactics strategies in teacher education programs.